P121 A self-management programme of activity coping and education – SPACE for COPD – in primary care: a pragmatic trial. (December 2018) - Bourne, C; Houchen-Wolloff, L; Kanabar, P; Bankart, M; Singh, S
Abstract : Background: National guidance for COPD suggests that self-management support should be provided for all patients. 1 We have previously developed a manual-based, supported self-management programme: Self-Management Programme of Activity Coping and Education-SPACE for COPD. Having previously piloted SPACE for COPD on a one-to-one basis, 2 stakeholders are also interested in delivering SPACE for COPD as a group-based programme facilitated by healthcare professionals (HCPs) within primary care. Aims: To examine whether group-based delivery of SPACE for COPD improves patient outcomes. Methods: A prospective, single-blinded, Randomised Controlled Trial was conducted, with follow-up at 6 months (6 M). Participants were assigned to a control (usual care) or intervention group (six-session, group-based SPACE for COPD delivered over 5 months). The primary outcome was symptom burden (COPD Assessment Test (CAT)). Secondary outcomes were knowledge (Bristol COPD Knowledge Questionnaire), quality of life (Chronic Respiratory Questionnaire (CRQ); EuroQol 5-Dimension), mood (Hospital Anxiety and Depression Scale), patient activation (Patient Activation Measure (PAM)) and exercise capacity (Incremental Shuttle Walk Test (ISWT); Endurance Shuttle Walk Test (ESWT)). Two-way ANOVAs were conducted to examine within-and between-group differences in outcomes. Results: 122 participants completed the CAT at baseline (BL) and 6 M (72% male, 70.7±8.2 years). CAT did not change between baseline and 6 M, and was not different between groups (intervention:15.0±7.6 vs 15.6±8.0; control:13.6±6.1 vs 15.6±7.8, p=0.181, for BL and 6 M respectively; table 1). Knowledge (intervention: 34.0±7.6 vs 37.6±7.8; control: 32.9±7.4 vs 33.8±8.2, p=0.027), CRQ fatigue (intervention:4.6±1.2 vs 4.8±1.4; control:4.7±1.2 vs 4.5±1.3, p=0.034), CRQ mastery (intervention:5.7±1.2 vs 6.0±1.1; control:5.9±1.1 vs 5.8±1.2, p=0.032), and patient activation (intervention:58.4±11.2 vs 63.5±15.3; control:59.7±10.6 vs 59.5±11.5, p=0.023) all significantly improved in the intervention group compared to the control group. Exercise capacity improved for the intervention group (ISWT: 413±155 vs 440±164, p=0.018; EWST: 497±397 vs 652±455, p<0.001, for BL and 6 M respectively). Conclusions: The SPACE for COPD intervention does not improve CAT, but does improve exercise capacity, patient activation, knowledge and quality of life domains 'fatigue' and 'mastery', when delivered as a group-based intervention by HCPs in the community. References: NICE. Chronic obstructive pulmonary disease in over 16s: diagnosis and management. NICE2010:CG101. Mitchell K, et al . A self-management programme for COPD: A randomised controlled trial. Eur Respir J European Respiratory Society 2014;44 :1538–47.